When and How the Punishment Must Fit the Crime - George J. Mailath; Volker Nocke; Lucy White (Center for Economic Studies and ifo Institute (CESifo), 2015)
In repeated normal-form (simultaneous-move) games, simple penal codes (Abreu, 1986, 1988) permit an elegant characterization of the set of subgame-perfect outcomes. We show that the logic of simple penal codes fails in repeated extensive-form games. By means of examples, we identify two types of settings in which a subgame-perfect outcome may be supported only by a profile with the property that the continuation play after a deviation is tailored not only to the identity of the deviator, but also to the nature of the deviation.
Keywords: C70; C72; C73; 330; simple penal code; subgame perfect equilibrium; repeated extensive game; optimal punishment